Impact of Acid Mine Drainage on the hydrogeochemical characteristics of the Tinto-Odiel Estuary (SW Spain) - Carro, B.; Borrego, J.; López-González, N.; Grande, J.A.; Gómez, T.; de la Torre, M.L.; Valente, T. (Journal of Iberian Geology, 2011)
pH and chlorinity content of estuarine water and behavior in the concentration of some heavy metals characteristics of acid mine drainage in the suspended matter and dissolved phase have allowed the identification of two mixing process in the Odiel-Tinto rivers estuary: a salt-induced mixing typical of marine estuaries and an acid neutralization process as a result of the mixture of acid fluvial water coming from the drainage basins, which are affected by acid mine drainage (AMD). Thus, the estuary is divided into three zones: (1) zone with acid water and with precipitation of sulphate phases during the beginning of the process of neutralization in the absence of salt-induced mixing, (2) zone with pH values between 4.5 and 7 where a removal of heavy metals in their dissolved phase is produced by coexistence of both mixture processes, and (3) zone where water is slightly basic and the salt-induced mixing produces a redissolution of some elements. Spatial location and extent of these zones within the estuarine system have seasonal variations depending on the volume of fluvial discharge.